(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر إنشاء المناطق الحرة بهدف توفير هياكل أساسية فعالة و القضاء على البيروقراطية ضمن نطاق محدد أداة شائعة الاستعمال لتعزيز الاستثمار الأجنبي المباشر الموجه نحو التصدير. و لكن أداء المناطق الحرة يعتمد إلى حد كبير على سياسات أخرى, و لاسيما السياسات الموضوعة لتنمية الموارد البشرية، و الهياكل الأساسية اللازمة لاجتذاب الاستثمار الأجنبي المباشر الموجه نحو التصدير و زيادته . و توجد مناطق حرة ناجحة في العالم في بلدان مثل الصين – كوريا – تايوان ، كما توجد مناطق حرة أخفقت في اجتذاب استثمارات هامة, حيث كانت التكاليف أكبر من الفوائد الاقتصادية و الاجتماعية . وهنا جاء بحثنا من أجل إعطاء فكرة أساسية من خلال تقييم عمل المناطق الحرة, و ذلك بتحليل الفوائد و التكاليف في ظل الأهداف و الغايات التي أنشأت من أجلها . The establishment of Free Zones in order to provide basic and efficient constructions and to get rid of bureaucracy in a limited range is considered a common means to enhance the direct foreign investment that is directed towards exportation. The performance of the Free Zones depends in a great deal on other policies , especially those that are established to develop the human resources and the basic constructions that are needed to attract and increase the direct foreign investment that is directed towards exportation. There are successful Free Zones in the world in countries such as (China – Korea – and Taiwan ) . There are also Free Zones that failed to attrack important investments where the expenses were more than the economic and social benefits . Hence This is why our research aims at giving an essential idea through evaluating the performance of the Free Zones through analyzing the benefits and expenses in the light of the goals and purposes for which they were basically established